2022
DOI: 10.33776/remo.vi18.6985
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Sports Tourists in Spain

Abstract: Sports tourism is a decisive factor in geographical mobility for leisure purposes. These activities entail certain acts and consequences inherent in their execution, which are worthy of study from the perspective of sustainable and reasonable tourism. Previous studies tried to show the characteristics of this type of tourist but did not provide relevant information to offer the necessary services to provide, to understand their patterns of habits, and to be able to act correctly. This paper aims to study the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Omar and collaborators showed that women give more importance to accommodation services when choosing a destination than men do [68], although a study of kayaking tourists in Poland showed that men place greater importance on accommodation than women [69]. Other research focusing on Spanish sports tourists found differences in distributions according to the type of accommodation chosen when analyzing gender [70]. By contrast, it has been shown that gender differences do not exist when it comes to the choice of shared accommodation [71].…”
Section: Discussionmentioning
confidence: 99%
“…Omar and collaborators showed that women give more importance to accommodation services when choosing a destination than men do [68], although a study of kayaking tourists in Poland showed that men place greater importance on accommodation than women [69]. Other research focusing on Spanish sports tourists found differences in distributions according to the type of accommodation chosen when analyzing gender [70]. By contrast, it has been shown that gender differences do not exist when it comes to the choice of shared accommodation [71].…”
Section: Discussionmentioning
confidence: 99%
“…Por su parte, el sector del empleo de estas empresas de turismo activo estará marcado, cada vez más, por su alta estacionalidad (Carrasco Jiménez, 2020). Con todos estos condicionantes y, coincidiendo con los empresarios de nuestro estudio, se persigue que la promoción del turismo activo esté condicionada a que los servicios y experiencias ofertadas sean de calidad y sostenibles en todo momento (Cánovas Pereda, 2018;Rojo-Ramos et al, 2020), siendo necesario el apoyo y respaldo de las diferentes instituciones y decretos reguladores para ello.…”
Section: Discussionunclassified